Associations between childhood sexual abuse, body image and the development of eating disorders - Svava Guðrún Helgadóttir 1992- (2016)
Sexual abuse is a fairly common and serious crime that affects significant number of both girls and boys and can lead to short and long term consequences affecting the victim’s health and functioning. Studies have revealed that there is a link between sexual abuse, negative body image and the development of eating disorders. The aim of the current study was to evaluate the effects of sexual abuse among girls and boys on body image and the development of eating disorders. The possible mediating effect of distorted body image was also examined as well as potential gender differences. The current data was collected by the Icelandic Centre for Social Research and Analysis as a part of their research Youth in Iceland 2007. In the current study responses from a random sample of 1.732 participants was used. The results showed that sexual abuse is associated with negative body image and eating disorders. The findings also showed that girls were more likely to self- report sexual abuse, have negative body image and eating disorders compared to boys. Furthermore, the study showed that body image partially mediated the effects of sexual abuse on eating disorders for girls. Keywords: Sexual abuse, body image, eating disorders, adolescents Kynferðislegt ofbeldi er fremur algengur en mjög alvarlegur glæpur sem framinn er gegn báðum kynum og getur leitt til alvarlegra skammtíma og langtíma afleiðinga sem hafa slæm áhrif á heilsu og virkni þeirra sem fyrir því verða. Rannsóknir hafa sýnt að það séu tengsl á milli kynferðislegs ofbeldis, neikvæðrar líkamsímyndar og þróun átraskana. Tilgangur rannsóknarinnar var að kanna tengsl kynferðislegs ofbeldis, líkamsímyndar og þróun átraskana á meðal stelpna og stráka. Hugsanleg miðlunarhrif líkamsímyndar voru einnig skoðuð. Gögnin sem notuð voru í rannsókninni voru fengin frá Rannsóknum og greiningu úr könnun þeirra Ungt fólk á Íslandi 2007. Valin voru af tilviljun 1.732 svör þátttakenda úr heildarþýði. Helstu niðurstöður rannsóknarinnar sýndu að kynferðislegt ofbeldi hefur neikvæða ...